Quantum Storage of Qubits in an Array of Independently Controllable Solid-State Quantum Memories - Markus Teller; Susana Plascencia; Samuele Grandi; Hugues de Riedmatten (Physical Review X)
Random-access quantum memories may offer computational advantages for quantum computers and networks. In this paper, we advance arrays of solid-state quantum memories toward their usage as random-access quantum memory. We perform quantum storage of path and time-bin qubits implemented with weak coherent states at the single-photon level, in an array of ten temporally multiplexed memory cells with controllable addressing. The qubits can be stored in arbitrary combinations of memory cells, from which they are read out on demand. We find average fidelities of 95_{-2}^{+2}% for path qubits and 91_{-2}^{+2}% for time-bin qubits. The measured fidelities violate the classical bounds for both encodings and for all ten cells. We also sequentially store a time-bin qubit in two different memory cells, maintain both qubits simultaneously in the array, and perform a collective readout. The individual control paired with high storage fidelity represents a significant advance toward a solid-state random-access quantum memory for quantum repeaters and photonic quantum processors.